Digital pathways to healthcare: a systematic review for unveiling the trends and insights in online health information-seeking behavior - Fu, Yang; Han, Ping; Wang, Jian; Shahzad, Fakhar (Frontiers in Public Health, 2025)
The importance of seeking online health information cannot be overstated when addressing public health concerns. Researchers must comprehensively review the literature on online health information seeking to fully comprehend the underlying behaviors and trends that shape this phenomenon. This systematic review utilizes bibliometric methodologies and the scientometric software CiteSpace to thoroughly analyze journals from the Web of Science core collection database (n = 2,761), providing the theoretical groundwork for future research in this field. Three main findings emerged from the analysis: first, research on online health information-seeking behavior has steadily increased, indicating that it is a hot topic in academia. Second, the convergence trend with emerging information technologies such as big data, artificial intelligence, and social media is changing user behavior and how people search for health information. Third, there is a growing emphasis on understanding how factors such as the digital divide, social media influence, public health initiatives, risk perception, and health anxiety affect online health information-seeking behavior. The research suggests potential areas for future investigation, such as emerging technologies, digital inequalities, social media analysis, public health implications, and psychological factors in health information-seeking. These areas have the potential to inform evidence-based interventions and advance the understanding of critical issues in healthcare.